Effect of pure sea-cucumberex1ract on healing process of closed simple long bone (tibia) fracture -animal study (rabbits) - Ab Rahman, Shaifuzain; Yusof, Halim; -, Hasnan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
For centuries, sea cucumber had been .claimed to promoteinternal and eMemal woun.d healing. Various researchers had shown the positive effects of sea cucumber (SC) in enhancing soft tissue repair. Unfortunately, little study was done to demonstrate the effect of sea cucumber on fracture healing. 10 adult New Zealand White rabbits, underwent tibial osteotomyto simulate fracture. The fracture was stabilised with intramedullary wiring and plaster cast. The subjects were divided into 3 groups. Th• first group received daily oral low dose SC extract ( l mg/Kg) and the second group was given daily oral high dose SC extract (!Omg/Kg). The extraet was prepared in liquid form to aid with oral administration. The last group was used as control. At 3 and 6 weeks., half of the subjects from each group were euthanised and the tibias were harvested and prepared lc>r histopathological assessment (HPE). Following the HPE. our study had shown that low dose SC promoted faster fracture healing when compared to the other groups. Meanwhile, high dose sea cucumber extract had lead to adverse outcome in delaying fracture healing as compared to the other 2 groups at both 3 and 6 weeks.